The influence of exercise interventions on cognitive functions in patients with amnestic mild cognitive impairment: A systematic review and meta-analysis - Wang, Rong; Zhang, Hanyue; Li, Hongjuan; Ren, Hong; Sun, Tingting; Xu, Liya; Liu, Yang; Hou, Xiao (Frontiers in Public Health, 2022)
Introduction Patients with amnestic mild cognitive impairment (aMCI) are more likely to develop dementia compared to patients with non-aMCI (naMCI). Among the mixed samples of aMCI and naMCI, exercise interventions are effective for patients with MCI to improve cognitive functions. However, the influence of exercise interventions on patients with aMCI is still unclear. Objective The objective of this systematic review and meta-analysis is to evaluate the influence of exercise interventions on cognitive functions in patients with aMCI. Methods Four literature databases (PubMed, Web of Science, EBSCO, and Cochrane Library) and three Chinese databases (China National Knowledge Infrastructure, Wanfang, and China Science and Technology Journal Database) were searched from their inception to August 31, 2022. Based on the preliminary search of seven databases and their cited references, a total of 2,290 records were identified. Finally, 10 studies with a total of 28 data points involving 575 participants with aMCI were included in this meta-analysis. If the measurements of outcomes were different among studies, the effect size was synthesized using the standardized mean difference (SMD) with a 95% confidence interval (CI). If the measurements were the same, the weight mean difference (WMD) with a 95% CI was used to integrate the effect size. Data synthesis The results showed that exercise interventions had no significant effects on improving several specific domains of cognitive functions including working memory (WMD = −0.05; 95% CI = −0.74 to 0.63; p = 0.88; I2 = 78%) and attention (SMD = 0.20; 95% CI = −0.31 to 0.72; p = 0.44; I2 = 60%). Additionally, exercise interventions had a significant effect on global cognitive function (SMD = 0.70; 95% CI = 0.50–0.90; p < 0.00001; I2 = 29%) and some specific cognitive domains including immediate recall (SMD = 0.55; 95% CI = 0.28–0.81; p < 0.0001; I2 = 0%), delayed recall (SMD = 0.66; 95% CI = 0.45–0.87; p < 0.00001; I2 = 37%), and executive function (SMD = 0.38; 95% CI = 0.16–0.60; p= 0.0006; I2 = 4%). Furthermore, subgroup analysis based on the intervention forms indicated that multi-component interventions (SMD = 0.44; 95% CI = 0.11–0.77; p = 0.009; I2 = 0%) appeared to be less effective than the single-component intervention (SMD = 0.85; 95% CI = 0.60–1.10; p < 0.00001; I2 = 10%) in terms of boosting global cognitive function. Conclusion This meta-analysis suggests that the exercise can help patients with aMCI improve global cognitive function. And exercise interventions have positive influence on enhancing several specific cognitive domains such as immediate recall, delayed recall, and executive function. Systematic review registration:http://www.crd.york.ac.uk/PROSPERO, identifier: CRD42022354235.